Challenges to the Recruitment and Retention of Volunteers in Traditional Nonprofit Organizations: A Case Study of Australian Meals on Wheels. Issue 16 (10th December 2018) - Warburton, Jeni; Moore, Melissa; Oppenheimer, Melanie
ABSTRACT: Australian Meals on Wheels (MoWs) is a well-known, traditional nonprofit organization operating for over 60 years in a mixed economy of welfare, where it is positioned between the increasingly complex demands of state regulation and market efficiency. These contextual challenges cause critical tensions to an organization reliant on humanitarian principles and a large volunteer workforce. Findings show that this organization is experiencing conflicting and multiple identities which are having a significant impact on volunteer recruitment and retention. Specifically, data highlight the external challenges that threaten volunteers relating to regulation and funding, and internal challenges that tend to ignore volunteer value and instead picture volunteers as ageing and resistant to change. Findings suggest that the organization needs to work with all stakeholders to develop a shared organizational identity that blends humanitarianism with managerialism. New inclusive processes can enable better recruitment and retention practices, enabling the organization to "unfreeze" its traditional ways of operating to build a sustainable future for this much-needed organization.